Anti-corrosion coating for marine environment and preparation method of anti-corrosion coating

By alternately depositing a multi-layer film structure on the surface of glass flakes, the precise release of corrosion inhibitors and high interfacial bonding strength are achieved, which solves the problem of rapid pitting and diffusion of the coating in marine environments and improves the corrosion resistance of the coating.

CN120665468APending Publication Date: 2025-09-19ZHONGKE WEIMIAO (QINGDAO) EQUIP TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510868185.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing marine environment anti-corrosion coatings are prone to rapid pitting corrosion spread due to local damage in high salt, acidic media and mechanical wear. The interface bonding between traditional glass flakes and the resin matrix is ​​weak and cannot actively inhibit corrosion spread. The corrosion inhibitor leakage rate is high and the response is insensitive.

Method used

Electrostatic layer-by-layer self-assembly technology is used to alternately deposit sodium polystyrene sulfonate and branched polyethyleneimine on the surface of glass flakes to form a multilayer film, embedding molybdate corrosion inhibitor, and cross-linking and curing with glutaraldehyde to form a multilayer film structure to achieve precise release of the corrosion inhibitor and high interfacial bonding strength.

Benefits of technology

When pH ≤ 5.0 or Cl- concentration ≥ 1.0M, the controllability of the corrosion inhibitor release rate reaches more than 90%, the coating adhesion is improved, the corrosion extension width is reduced, and the corrosion resistance of the coating is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an anticorrosive coating for a marine environment and a preparation method thereof, the anticorrosive coating comprises a modified glass flake, a coating matrix and a curing agent, the modified glass flake comprises a glass flake and a multilayer film, the multilayer film is formed by a cationic polyelectrolyte layer and an anionic polyelectrolyte layer which are alternately deposited on the surface of the glass flake, a corrosion inhibitor is embedded between each cationic polyelectrolyte layer and each anionic polyelectrolyte layer, and the cationic polyelectrolyte layers are cross-linked and cured by adopting a cross-linking agent after the corrosion inhibitor is embedded. The invention aims to solve the problems of weak interface bonding, high corrosion inhibitor leakage rate and insensitive trigger release of the traditional marine anticorrosive paint. A multi-layer polyelectrolyte membrane-corrosion inhibitor composite structure is constructed on the surface of a glass flake through an electrostatic layer-by-layer self-assembly technology, accurate on-demand release of a corrosion inhibitor is achieved, meanwhile, the interface bonding force and corrosion resistance of a coating are remarkably improved, and the problem of rapid pitting diffusion of local damage of traditional anticorrosive paint is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coatings, and more particularly to an anti-corrosion coating for use in marine environments and a preparation method thereof. Background Art

[0002] In the marine environment, metal structures such as ships, port facilities, and offshore oil and gas platforms are exposed to high salt (Cl - Multiple corrosion challenges, including corrosion in the presence of ferrous metals (concentrations exceeding 1.0M), acidic media (local pH ≤ 5.0), and mechanical wear, severely impact the performance and service life of steel, posing significant safety risks over time. Currently, a variety of metal corrosion protection technologies are available, including electrochemical, electroplating, and organic coatings. Organic coatings are a key technology in this field, offering advantages such as convenient construction, low cost, and easy maintenance. However, under harsh operating conditions (high salt spray, acidic media, and mechanical wear), localized coating damage can easily lead to rapid pitting and corrosion spread, becoming a key bottleneck restricting the coating's long-term protective performance.

[0003] Traditional glass flakes, arranged in parallel, create a "maze effect" that can enhance the barrier properties of coatings. However, their interfacial bonding with the resin matrix is ​​weak, and they only provide a passive barrier function, failing to actively inhibit the spread of corrosion. While existing technologies have attempted to modify glass flakes with silane coupling agents to enhance interfacial bonding, this still fails to address the issue of actively inhibiting corrosion spread. Other attempts to directly load corrosion inhibitors have resulted in high inhibitor leakage rates and insensitive trigger responses. Therefore, developing a marine anticorrosive coating that combines high interfacial bonding with precise inhibitor release is crucial. Summary of the Invention

[0004] In view of the various deficiencies of the existing technology, in order to solve the above problems, an anti-corrosion coating for marine environment and its preparation method are proposed, and the following technical solutions are provided: An anti-corrosion coating for marine environments includes modified glass flakes, a coating matrix and a curing agent. The modified glass flakes include glass flakes and a multilayer film. The multilayer film is formed by cationic polyelectrolyte layers and anionic polyelectrolyte layers alternately deposited on the surface of the glass flakes. A corrosion inhibitor is embedded between each cationic polyelectrolyte layer and each anionic polyelectrolyte layer. After the corrosion inhibitor is embedded, the cationic polyelectrolyte layer is cross-linked and cured using a cross-linking agent.

[0005] Furthermore, the anionic polyelectrolyte layer is a sodium polystyrene sulfonate layer, the cationic polyelectrolyte layer is a branched polyethyleneimine layer, and the number of layers of the anionic polyelectrolyte layer and the cationic polyelectrolyte layer are both 5-20.

[0006] Furthermore, the number of the anionic polyelectrolyte layer is 5-20, and the number of the cationic polyelectrolyte layer is 5-20.

[0007] Furthermore, the cross-linking agent is a glutaraldehyde solution, and the corrosion inhibitor is a molybdate solution.

[0008] Furthermore, the concentration of the molybdate solution is 8-12 mg / mL, and the concentration of glutaraldehyde is 0.1-2% v / v.

[0009] Furthermore, the preparation steps of the modified glass flakes include: (a) acid washing, water washing and plasma activation treatment of glass flakes; (b) immersing the glass flakes obtained in step (a) in a cationic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (c) immersing the glass flakes treated in step (b) in an anionic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a molybdate solution, shaking for 10-15 minutes, then washing with water and drying; (e) immersing the glass flakes obtained in step (d) again in the cationic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (f) Repeat steps (c) to (e) 5-20 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a glutaraldehyde aqueous solution and shaken for 50-60 minutes, washed with water, and dried to obtain modified glass flakes.

[0010] Furthermore, the concentration of the cationic polyelectrolyte solution in steps (b) and (e) is 1-1.5 mg / mL, and the concentration of the anionic polyelectrolyte solution in step (c) is 1-1.5 mg / mL.

[0011] Furthermore, the coating matrix is ​​epoxy resin.

[0012] In addition, the present invention also provides a method for preparing the above-mentioned anti-corrosion coating for marine environment, which comprises stirring and mixing deionized water, dispersant and defoaming agent, adding modified glass flakes three times after adding the coating matrix and stirring and mixing, and adding curing agent and stirring after mixing to obtain the anti-corrosion coating.

[0013] Furthermore, calculated by mass, the coating base is 60-90 parts, the modified glass flakes are 10-40 parts, the dispersant is 0.3-0.8 parts, the defoaming agent is 0.1-0.5 parts, the curing agent is 10-20 parts, and the deionized water is 1-2 parts.

[0014] Due to the adoption of the above technical solution, the beneficial technical effects of the present invention are: 1. The present invention forms a multilayer film by alternately depositing sodium polystyrene sulfonate and branched polyethyleneimine on the surface of glass flakes through electrostatic layer-by-layer self-assembly technology, embedding molybdate corrosion inhibitor in each layer of sodium polystyrene sulfonate and branched polyethyleneimine, and then cross-linking and curing with glutaraldehyde. The multilayer film structure is formed by the sulfonic acid group (-SO3 - ) is protonated (-SO3H) under acidic conditions and high Cl - The electrostatic shielding effect caused by concentration can achieve pH ≤ 5.0 or Cl - Precise release at concentrations ≥1.0M.

[0015] 2. The multilayer film structure precisely embeds the corrosion inhibitor in the nanoscale space, and combines with glutaraldehyde cross-linking to inhibit leakage. The corrosion inhibitor embedding operation is performed after the adsorption of sodium styrene sulfonate and before the adsorption of branched polyethyleneimine, further preventing the leakage of the corrosion inhibitor.

[0016] 3. The plasma-activated glass flakes are bonded to the multilayer film through electrostatic interaction, and the primary amine groups in the branched polyethyleneimine form chemical bonds with the epoxy resin matrix, thereby improving the interfacial bonding strength and corrosion resistance of the coating. DETAILED DESCRIPTION

[0017] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the embodiments of the present invention. Based on the embodiments in this application, other similar embodiments obtained by ordinary technicians in this field without making any creative work should fall within the scope of protection of this application.

[0018] An anti-corrosion coating for marine environments, comprising modified glass flakes, a coating matrix, and a curing agent. The modified glass flakes comprise glass flakes and a multilayer film, wherein the multilayer film is formed by alternating cationic polyelectrolyte layers and anionic polyelectrolyte layers deposited on the surface of the glass flakes, wherein a corrosion inhibitor is embedded between each cationic polyelectrolyte layer and each anionic polyelectrolyte layer, and after embedding the corrosion inhibitor, the cationic polyelectrolyte layer is cross-linked and cured using a cross-linking agent. The present invention uses electrostatic layer-by-layer self-assembly technology to alternately deposit cationic polyelectrolyte layers and anionic polyelectrolyte layers on the surface of the glass flakes to form a multilayer film, embeds a molybdate corrosion inhibitor in each layer of sodium polystyrene sulfonate and branched polyethyleneimine, and then cross-links and cures with glutaraldehyde. This structure can achieve corrosion inhibition at pH ≤ 5.0 or Cl - Precise on-demand release at ≥1.0M, with a release rate controllable over 90%. The prepared anti-corrosion coating has reduced scratch corrosion extension width and improved adhesion after 1000h of salt spray.

[0019] The glass flakes were 3-5 μm thick and 20-50 μm in diameter. They were washed in 5% HCl for 30 min and then washed with deionized water until neutral. They were dried at 120°C and plasma treated (O2, 100W, 5 min) to enhance the surface negative charge.

[0020] The cationic polyelectrolyte layer is a branched polyethyleneimine layer. The branched polyethyleneimine has Mw=25kDa, 1 mg / mL, pH=7.5, high charge density, good film-forming properties, and contains primary amino groups for subsequent cross-linking.

[0021] The anionic polyelectrolyte layer is a sodium polystyrene sulfonate layer with Mw = 70 kDa, 1 mg / mL, pH = 7.5. Sodium polystyrene sulfonate has strong anionic properties.

[0022] The corrosion inhibitor is molybdate solution, in the form of anions (MoO 2- ) is easily embedded after sodium styrene sulfonate adsorption and before branched polyethyleneimine adsorption.

[0023] When the local pH of the coating decreases (such as the cathode reaction produces H + ), the sulfonic acid group in sodium polystyrene sulfonate is protonated (-SO3 - →-SO3H), the electrostatic repulsion weakens, the film swells, MoO4 2- Diffusion channels open to accelerate release.

[0024] High concentration of Cl - After invading the membrane, the electrostatic attraction between the cationic polyelectrolyte layer and the anionic polyelectrolyte layer is shielded, causing the membrane to dissociate. 2- Released with the ion flow.

[0025] Example 1 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0026] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 20 min → wash with water three times → blow dry with N2; (c) Immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1 mg / mL + 0.5 M NaCl, pH 7.5), shaking for 25 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a 10 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) 10 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 0.5% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0027] Example 2 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0028] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 20 min → wash with water three times → blow dry with N2; (c) Immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1 mg / mL + 0.5 M NaCl, pH 7.5), shaking for 25 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a 10 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) 5 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 0.5% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0029] Example 3 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0030] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 20 min → wash with water three times → blow dry with N2; (c) Immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1 mg / mL + 0.5 M NaCl, pH 7.5), shaking for 25 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a 10 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) 20 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 0.5% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0031] Example 4 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0032] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1.5 mg / mL) and shake for 20 min → wash with water three times → blow dry with N2; (c) immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1.5 mg / mL + 0.5 M NaCl), shaking for 20 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in an 8 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) 10 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 0.1% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0033] Example 5 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0034] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 30 min → wash with water three times → blow dry with N2; (c) immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1 mg / mL + 0.5 M NaCl, pH 7.5), shaking for 30 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a 12 mg / mL sodium molybdate solution, shaking for 10 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 30 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) 10 times; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 2% glutaraldehyde aqueous solution and shaken for 50 minutes, washed with water, and dried to obtain modified glass flakes.

[0035] Comparative Example 1 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were washed with 5% HCl for 30 min, washed with water until neutral, dried at 120 °C, and then treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min. Γ-methacryloxypropyltrimethoxysilane are added into water and stirred to obtain modified glass flakes.

[0036] Comparative Example 2 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0037] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 20 min → wash with water three times → blow dry with N2; (c) Immersing the glass flakes treated in step (b) in a sodium polystyrene sulfonate solution (1 mg / mL + 0.5 M NaCl, pH 7.5), shaking for 25 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a 10 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (e) The glass flakes obtained in step (d) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (f) Repeat steps (c) to (e) twice; (g) Cross-linking and curing: the glass flakes obtained in step (f) are immersed in a 0.5% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0038] Comparative Example 3 Preparation of modified glass flakes: (a) 20 g of glass flakes (5 μm × 50 μm) were cleaned with 5% HCl by oscillation for 30 min, then washed with water until neutral, dried at 120°C, and treated in a plasma cleaner (O2, 100 Pa, 100 W) for 5 min.

[0039] (b) Immerse the glass flakes obtained in step (a) in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) and shake for 20 min → wash with water three times → blow dry with N2; (c) immersing the glass flakes obtained in step (b) in a 10 mg / mL sodium molybdate solution, shaking for 15 minutes, then washing with water and drying; (d) The glass flakes obtained in step (c) were immersed in a branched polyethyleneimine solution (1 mg / mL, pH 7.5) again, shaken for 25 minutes, washed with water, and dried; (e) Repeat steps (b) to (d) 10 times; (f) Cross-linking and curing: the glass flakes obtained in step (e) are immersed in a 0.5% glutaraldehyde aqueous solution and shaken for 60 minutes, washed with water, and dried to obtain modified glass flakes.

[0040] The modified glass flakes obtained in Examples 1-5 and Comparative Examples 1-3 were tested for corrosion inhibitor loading, and the test results are shown in Table 1 below.

[0041] The test method is as follows: Take 50 mg of modified glass flakes from each example and comparative example; Acid hydrolysis extraction: Dissolve with 5% HNO3 solution for 48 hours to completely release the embedded MoO4 2- ICP-OES detection: Determine the molybdenum content in the solution and calculate the loading rate (wt% = molybdenum mass / scale mass × 100%).

[0042] Table 1 Test results of modified glass flake corrosion inhibitor loading obtained in Examples 1-5 and Comparative Examples 1-3 The loading rate of the examples of this application is significantly higher than that of all the comparative examples, proving the necessity of the alternating deposition structure designed in this application for high loading. The loading rate of Example 1 reaches 16.5 wt%, which is 101-189% higher than that of Comparative Examples 1-3.

[0043] The modified glass flakes obtained in Example 1 and Comparative Examples 2 and 3 were subjected to a corrosion inhibitor release controllability test, and the test results are shown in Table 2 below.

[0044] Test method: Place the modified flakes in three solutions (500 mL each) and shake at a constant temperature of 37°C: Neutral environment: 3.5% NaCl (pH=7.0) Acidic environment: 3.5% NaCl + HCl (pH=4.0) High salt environment: 5.0M NaCl (pH=7.0) The Mo release was detected by ICP-OES at regular intervals and the cumulative release rate was calculated.

[0045] Table 2 Test results of release controllability of modified glass flakes obtained in Example 1 and Comparative Examples 2 and 3 Example 1 exhibited a release rate of >80% when triggered in a corrosive environment, while Comparative Examples 2-3 exhibited a sluggish response. Comparative Example 3 exhibited an extremely high leakage rate (68%) in a non-triggered environment, demonstrating no failure of the anionic layer structure. Example 1 exhibited a release rate of >80% in acidic and high-salt conditions, with leakage of <5% in a neutral environment.

[0046] The modified glass flakes obtained in Examples 1-5 and Comparative Examples 1-3 were used to prepare anti-corrosion coatings. The method for preparing the anti-corrosion coatings is as follows: 1.5 parts of deionized water, 0.5 parts of sodium dodecylbenzenesulfonate as a dispersant, and 0.3 parts of polyether-modified polysiloxane as a defoamer were added to 10 parts of modified glass flakes and stirred and mixed. 80 parts of epoxy resin were added, followed by 10 parts of modified glass flakes, and the mixture was stirred and mixed for 10 minutes. Finally, 10 parts of modified glass flakes were added, and after mixing, 15 parts of polyamide as a curing agent was added and stirred to obtain an anti-corrosion coating. The obtained anti-corrosion coatings were coating 1, coating 2, coating 3, coating 4, coating 5, coating 6, coating 7, and coating 8.

[0047] The modified glass flakes obtained in Example 1 were used to prepare an anticorrosive coating. The method for preparing the anticorrosive coating was as follows: 1 part of deionized water, 0.3 parts of sodium dodecylbenzenesulfonate as a dispersant, and 0.1 parts of polyether-modified polysiloxane as a defoamer were added to 3.33 parts of the modified glass flakes and stirred and mixed. 60 parts of epoxy resin were added, followed by 3.33 parts of the modified glass flakes, and the mixture was stirred and mixed for 10 minutes. Finally, 3.33 parts of the modified glass flakes were added. After mixing, 10 parts of polyamide as a curing agent were added and stirred to obtain the anticorrosive coating. The obtained anticorrosive coatings were designated as coating 9.

[0048] The modified glass flakes obtained in Example 1 were used to prepare an anticorrosive coating. The method for preparing the anticorrosive coating was as follows: 2 parts of deionized water, 0.8 parts of sodium dodecylbenzenesulfonate as a dispersant, and 0.5 parts of polyether-modified polysiloxane as a defoamer were added to 13.33 parts of the modified glass flakes, and the mixture was stirred and mixed. 90 parts of epoxy resin was added, followed by 13.33 parts of the modified glass flakes, and the mixture was stirred and mixed for 10 minutes. Finally, 13.33 parts of the modified glass flakes were added, and after mixing, 20 parts of polyamide as a curing agent were added and stirred to obtain the anticorrosive coating. The obtained anticorrosive coatings were respectively designated as coating 10.

[0049] An anticorrosive coating was prepared using the modified glass flakes obtained in Example 1. The method for preparing the anticorrosive coating was as follows: 1.5 parts of deionized water, 0.5 parts of sodium dodecylbenzenesulfonate as a dispersant, and 0.3 parts of polyether-modified polysiloxane as a defoamer were stirred and mixed. 80 parts of epoxy resin were added, followed by 30 parts of the modified glass flakes. After mixing, 15 parts of polyamide as a curing agent were added and stirred to obtain the anticorrosive coating. The resulting anticorrosive coating was designated as Coating 11.

[0050] The performance of coating 1 to coating 11 was tested: 1. Aging test: After the paint is applied to the sample to form a film, the adhesion of the coating film is tested by the pull-off method. Then, the sample is immersed in seawater for 4200 hours for aging test in accordance with ISO2812-2:2018. After the aging test, the adhesion of the coating film is tested by the pull-off method.

[0051] 2. Corrosion resistance: Refer to ASTM D1654-92 "Evaluation of Painted Specimens Subjected to Corrosive Environments" and record the average corrosion spread at the scratch on the coating on the sample. The average corrosion spread M = (CW) / 2, where C is the average corrosion width of 9 sampling points at the scratch on the same sample, and W is the initial width of the scratch.

[0052] The test results are shown in Table 3.

[0053] Table 3 Anticorrosion performance test results of coatings 1 to 11 First, through the design of alternating multilayer deposition, coatings 1-5 exhibit significantly better adhesion than the other coatings, both before and after aging. Second, the average corrosion propagation of coatings 1-5 is lower than that of coatings 6-8, with coating 1-5 exhibiting superior scratch corrosion inhibition compared to coatings 6-8. Furthermore, the scratch corrosion inhibition effect can be modified by adjusting the coating ratio and addition method, particularly when the modified glass flakes are added in three separate additions.

[0054] The present invention achieves precise release and high loading of corrosion inhibitors through a multi-layer polyelectrolyte membrane structure, while enhancing the interfacial bonding strength of the coating, exhibiting excellent corrosion resistance in harsh marine environments, and possesses significant innovation and practicality.

[0055] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. An anti-corrosion coating for marine environment, characterized in that: The invention comprises modified glass flakes, a coating matrix and a curing agent. The modified glass flakes comprise glass flakes and a multilayer film. The multilayer film is formed by cationic polyelectrolyte layers and anionic polyelectrolyte layers alternately deposited on the surface of the glass flakes. A corrosion inhibitor is embedded between each cationic polyelectrolyte layer and each anionic polyelectrolyte layer. After the corrosion inhibitor is embedded, the cationic polyelectrolyte layer is cross-linked and cured using a cross-linking agent.

2. The anti-corrosion coating for marine environment according to claim 1, characterized in that: The anionic polyelectrolyte layer is a sodium polystyrene sulfonate layer, the cationic polyelectrolyte layer is a branched polyethyleneimine layer, and the number of layers of the anionic polyelectrolyte layer and the cationic polyelectrolyte layer are both 5-20.

3. The anti-corrosion coating for marine environment according to claim 1, characterized in that: The anionic polyelectrolyte layer has 5 to 20 layers, and the cationic polyelectrolyte layer has 5 to 20 layers.

4. The anti-corrosion coating for marine environment according to claim 1, characterized in that: The cross-linking agent is glutaraldehyde solution, and the corrosion inhibitor is molybdate solution.

5. The anti-corrosion coating for marine environment according to claim 4, characterized in that: The concentration of molybdate solution is 8-12 mg / mL, and the concentration of glutaraldehyde is 0.1-2% v / v.

6. The anti-corrosion coating for marine environment according to claim 1, characterized in that: The preparation steps of modified glass flakes include: (a) acid washing, water washing and plasma activation treatment of glass flakes; (b) immersing the glass flakes obtained in step (a) in a cationic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (c) immersing the glass flakes treated in step (b) in an anionic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (d) immersing the glass flakes obtained in step (c) in a molybdate solution, shaking for 10-15 minutes, then washing with water and drying; (e) immersing the glass flakes obtained in step (d) again in the cationic polyelectrolyte solution, shaking for 20-30 minutes, then washing with water and drying; (f) Repeat steps (c) to (e) 5-20 times; (g) Cross-linking and curing: immerse the glass flakes obtained in step (f) in a glutaraldehyde aqueous solution and shake for 50-60 minutes, then wash with water and dry to obtain modified glass flakes.

7. The anti-corrosion coating for marine environment according to claim 6, characterized in that: The concentration of the cationic polyelectrolyte solution in steps (b) and (e) is 1-1.5 mg / mL, and the concentration of the anionic polyelectrolyte solution in step (c) is 1-1.5 mg / mL.

8. The anti-corrosion coating for marine environment according to claim 1, characterized in that: The coating matrix is ​​epoxy resin.

9. The method for preparing the anticorrosive coating for marine environment according to any one of claims 1 to 8, characterized in that: Deionized water, dispersant and defoamer are stirred and mixed, and after adding the coating base, modified glass flakes are added three times and stirred and mixed. After mixing, a curing agent is added and stirred to obtain an anti-corrosion coating.

10. The method for preparing an anti-corrosion coating for marine environment according to claim 9, characterized in that: Calculated by mass, the coating base is 60-90 parts, the modified glass flakes are 10-40 parts, the dispersant is 0.3-0.8 parts, the defoaming agent is 0.1-0.5 parts, the curing agent is 10-20 parts, and the deionized water is 1-2 parts.